CONCEPT OF A MECHATRONIC MODULE FOR INTELLIGENT COOLING OF CUTTING TOOLS FOR CNC LATHES - TYMOSHCHUK, OLEKSANDR; KOZYAR, MYKOLA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Existing cutting tool cooling systems on CNC machines are typically adaptations of traditional methods used on manually operated machines. The coolant supply is carried out without taking into account the thermal processes in the cutting zone, which leads to limited control capabilities and uneven heat dissipation. This, in turn, has a negative impact on tool life, workpiece surface finish and machining accuracy. Automating the turning process on CNC machines requires efficient cutting tool cooling systems to increase productivity and improve machining quality. The aim of this paper is to substantiate the concept of a mechatronic module for intelligent cooling of cutting tools in CNC metalworking lathes with dual temperature control of coolant, cutting tool and air. The concept of the module is based on an in-depth analysis of the sources of cutting tool heating and the development of a system that provides adaptive control of the cooling process. The key features of the proposed solution are: dual thermometry (simultaneous monitoring of the temperature of the cooling liquid, cutting tool and cutting zone ensures accurate monitoring of thermal processes); adaptive control (depending on the temperature data obtained, the system automatically adjusts the cooling intensity, ensuring optimal tool operation conditions); energy efficiency (due to intelligent control, the module allows efficient use of cooling resources, reducing energy consumption); and It is believed that the proposed concept of the mechatronic module will allow to: increase the service life of the cutting tool; improve the quality of the machined surface; increase machining accuracy; reduce equipment maintenance costs; and increase machine productivity. The introduction of such a module is a promising area for the development of turning technologies, as it will increase production efficiency and reduce production costs. Further research is seen in expanding the functionality of the module, optimizing its operation for different types of cutting tools and materials, and developing intelligent control systems (microcontroller control software).
Keywords: CNC machine; mechatronics; mechatronic module; tool cooling; process thermometry